Organic geochemical chracteristics of Alpagut-Dodurga (Corum) coals - Yalcin Erik, Nazan; Aslan, Yasemin; Buyuksarac, Aydin (Pamukkale Univ, 2018)
This study have been conducted to evaluate the hydrocarbon potential and plus paleodepositional environmental characteristics of Lower-Middle Miocene aged Sub Bituminous coal located in Cankiri-Corum Basin. In this context, compiled representation of the coal samples from the three coal fields from Northern Corum (Incesu, Evlik and Alpagut-Dodurga) were performed as detailed organic geochemical and organic petrographic analysis. Organic geochemical evaluations utilizing TOC-Rock-Eval pyrolysis analysis, GC, GC-MS analysis are performed and determined the amount of organic matter that formed the coals, type and effective agents in the coal formation process. Results of the Rock-Eval analysis of coal samples indicate that the dominant kerogen type III and type II/III. Organic compounds of coals consist of mainly huminite group macerals, and lesser liptinite and inertinite groups. According to petrographic and biomarker data of these coals, depositional environment was the reeds/forest swamp or a lake swamp. Although the probability of such an occurrence, rather than gas derived from petroleum potential for organic matter content and type of coal is very low due to the low maturity.
Keywords: Tertiary coals; Cankiri-Corum basin; Organic geochemistry; Biomarkers; Organic petrography